Pengaruh Gaya Kepemimpinan Demokratik Dan Fasilitas Kesehatan Terhadap Kepuasan Pasien Pada Uptd Puskesmas Nusa Penida I Kabupaten Klungkung - I Ketut Merta; I Dewa Nyoman Usadha; I Nyoman Purna (Universitas Mahendradatta Denpasar, 2020)
This study entitled The Effect of Leadership Style and Health Facilities on Patient Satisfaction and the object of research at the Nusa Penida I Public Health Center in Nusa Penida, Klungkung Regency. The aim is to examine the influence of leadership style, health facilities and patient satisfaction. Methodology: Population 396 For three months starting January-March and using a sample of 80 respondents, using a questionnaire, with validity and reliability tests, correlation analysis, and simultaneous significance test (F test), partial significance test (t-test) using multiple linear regression , assisted by SPSS Software version 24. The hypothesis in this study uses three hypotheses with the results Hypothesis1. The variable of leadership style and health facility variables with the F-count test simultaneously